2018
DOI: 10.2298/jmmb171002020a
|View full text |Cite
|
Sign up to set email alerts
|

The particle size distribution (PSD) as criteria for comparison of silver powders obtained by different methods of synthesis and by conditions of electrolysis

Abstract: Silver powders produced by both electrochemical (galvanostatic (DC) and potentiostatic (POT) regimes of electrolysis) and chemical processes were examined by scanning electron microscope, and particle size distribution (PSD) of the obtained particles was done. In the DC regime, the current densities of-14.4 mA cm-2 for the nitrate (NIT; powder denoted with DC(NIT)) and-13.05 mA cm-2 for the ammonium (AM; DC(AM)) electrolytes were applied. In the POT regime, the used overpotentials were-90 mV (NIT(90)) and-150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The increase in the current density after an electrolysis time of 15 min indicates to the formation and growth of dendrites. 22 The real current density remains constant, while the electrode surface area increases with time and as a result, the current density increases with time in the potentiostatic regime of electrolysis. 19,23 The attained amounts of electricity of 2.4 and 4.8 mA h cm -2 are denoted by vertical lines in Fig 1a. The chrono-potentiometric dependence obtained at a current density of 14.4 mA cm -2 is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the current density after an electrolysis time of 15 min indicates to the formation and growth of dendrites. 22 The real current density remains constant, while the electrode surface area increases with time and as a result, the current density increases with time in the potentiostatic regime of electrolysis. 19,23 The attained amounts of electricity of 2.4 and 4.8 mA h cm -2 are denoted by vertical lines in Fig 1a. The chrono-potentiometric dependence obtained at a current density of 14.4 mA cm -2 is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Serum and Plasma of semen fructosamine by NBTspectrophotometric method (14) . The concentrations of K, Mg, and Zn in serum and seminal plasma detected with Electrolyte Analyzer-PSD (14) and the hormones assayed using multi-parametric immune analyzer MINI VIDAS® automated immunoassay system by Biomerix (France) (15) . Data will represent as Mean ± SD and analyze using SPSS software.…”
Section: Mbg =176*(hba1c) -367mmol/l P-hba1c = 0017*fa + 161 Gg = M-h...mentioning
confidence: 99%
“…Pulsing electrolysis is a method to produce high purity nano powder that has been applied for producing nanosized copper powders [23]. It has been reported that by utilizing different regimes of electrolysis which are galvanostatic and potentiostatic, and by chemical route using hydrazine as reduction agent, various shapes and size distribution of silver powder have been obtained [24].…”
Section: J Min Metall Sect B-metall 55 (2) B (2019) 261 -270mentioning
confidence: 99%